2015
DOI: 10.1152/jn.00576.2015
|View full text |Cite
|
Sign up to set email alerts
|

Parallel updating and weighting of multiple spatial maps for visual stability during whole body motion

Abstract: It is known that the brain uses multiple reference frames to code spatial information, including eye-centered and body-centered frames. When we move our body in space, these internal representations are no longer in register with external space, unless they are actively updated. Whether the brain updates multiple spatial representations in parallel, or whether it restricts its updating mechanisms to a single reference frame from which other representations are constructed, remains an open question. We develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Previous research has investigated spatial updating across body translation in complete darkness using psychophysical procedure where participants have to compare the position of a probe target to a reference [17,19]. Despite the similarity with our test trials where a probe target was shown at the end of the translation, the aim of these studies was in fact closer to the goal of our updating-only trials: measuring how an observer updates an object position based on vestibular cues only.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated spatial updating across body translation in complete darkness using psychophysical procedure where participants have to compare the position of a probe target to a reference [17,19]. Despite the similarity with our test trials where a probe target was shown at the end of the translation, the aim of these studies was in fact closer to the goal of our updating-only trials: measuring how an observer updates an object position based on vestibular cues only.…”
Section: Discussionmentioning
confidence: 99%
“…Model fits revealed that an object-based reference frame could also contribute to spatial updating. This speaks to the notion that the brain defines line information in multiple reference frames in parallel, perhaps depending on their reliability (McGuire & Sabes, 2009;Tramper & Medendorp, 2015). In this study, the visual frame had only a minor contribution to the updating performance.…”
Section: Discussionmentioning
confidence: 60%
“…If one of the references changes, the spatial relationship needs to be recomputed to maintain a correct registry with its true spatial orientation in the world. This is referred to as spatial updating, and has been studied extensively in relation to single points (Baker, Harper, & Snyder, 2013;Bloomberg, Jones, Segal, McFarlane, & Soul, 1988;Clemens, Selen, Koppen, & Medendorp, 2012;Gutteling, Selen, & Medendorp, 2015;Israël, Ventre-Dominey, & Denise, 1999;Klier & Angelaki, 2008;Tramper & Medendorp, 2015;Van Pelt, Van Gisbergen, & Medendorp, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the body moves, these body-centered representations are also no longer in register with external space, unless they are actively updated. Recently, we addressed the question of whether the state estimator updates the representations in the various reference frames simultaneously, or whether it relies on a single frame for updating, from which representations in other reference frame are subsequently constructed (Tramper and Medendorp, 2015).…”
Section: State Estimation Based On Multiple Coordinate Representationsmentioning
confidence: 99%